86.2k views
3 votes
PLEASE HURRY

What is the solution to the equation 3(x – 1) – 2(2x + 1) = 8(x – 1)? x = -4/7. x = 3/7 x = 1/3 x = 2/3

User Mesqueeb
by
5.4k points

1 Answer

3 votes

Answer:

x =
(1)/(3)

Explanation:

Distribute parenthesis on both sides of the equation.

3x - 3 - 4x - 2 = 8x - 8 ← simplify left side

- x - 5 = 8x - 8 ( subtract 8x from both sides )

- 9x - 5 = - 8 ( add 5 to both sides )

- 9x = - 3 ( divide both sides by - 9 )

x =
(-3)/(-9) =
(3)/(9) =
(1)/(3)

User Narendra Prasath
by
5.6k points